Efektivitas TENS untuk Menurunkan Tingkat Nyeri dan Meningkatkan Fungsional pada Remaja dengan Dismenore: : Critical Review - Faradilla, Arvindha; Wahyuni, Wahyuni (Griya Widya: Journal of Sexual and Reproductive Health, 2023)
Background: Adolescence in girls is marked by menstruation. It sometimes occurs with abnormalities, physical changes in the reproductive organs during adolescence are influenced by the maturation of sexual hormones. Menstruation is generally associated with some discomfort and minor complaints of illness. One of them is dysmenorrhea. To treat dysmenorrhea, non-pharmacological therapy is used, namely TENS (Transcutaneous Electrical Nerve Stimulation). TENS is like passing an electric current to the surface of the skin through an electrode and triggering the tissue found in the muscle. Purpose: To review the effectiveness of TENS to reduce pain and improve function in adolescents with dysmenorrhea. Method: The research method of this study, namely a critical review of scientific articles published in the 2012-2022 range with the type of study in the form of a Randomized Controlled Trial (RCT). The appraisal stage uses the PEDro Scale Checklist. Result: Based on data obtained from a review of three articles, three of them had a moderate risk of bias and 3 were of good quality. Conclusion: Based on the results of a critical review of six selected articles, TENS is effective in reducing diseases and symptoms associated with dysmenorrheal pain.